Forcing Ladderenes into Plastic Semiconductors with Mechanochemistry. - Thomas, Samuel W., III. (Tufts University. Tisch Library., 2018)
May the force be with you: Xia, Burns, Martinez, and co-workers harnessed the ring strain of ladderenes to enable both their polymerization and mechanochemical unzipping to yield semiconducting polyacetylene-based block copolymers. These materials have promise as functional polymers for applications such as detection of physical stress.